2017
DOI: 10.1021/acs.langmuir.7b02123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interaction of Nanoparticles and Surfactants on the Spreading Dynamics of Sessile Droplets

Abstract: While a body of literature on the spreading dynamics of surfactants and a few studies on the spreading dynamics of nanocolloids exist, to the best of the authors' knowledge, there are no reports on the effect of presence of surfactants on the spreading dynamics of nanocolloidal suspensions. For the first time the present study reports an extensive experimental and theoretical study on the effect of surfactant impregnated nanocolloidal complex fluids in modulating the spreading dynamics. A segregation analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
(76 reference statements)
1
28
0
Order By: Relevance
“…They found that a slower surfactant supply from the bulk towards the leading edge leads to a Marangoni flow towards the three phase contact line, resulting in faster spreading. In their case, the surfactant showed the opposite influence on wetting compared to [5].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…They found that a slower surfactant supply from the bulk towards the leading edge leads to a Marangoni flow towards the three phase contact line, resulting in faster spreading. In their case, the surfactant showed the opposite influence on wetting compared to [5].…”
Section: Introductionmentioning
confidence: 94%
“…However, typical inks show a more complex behavior due to the presence of the pigments and surface active substances, so-called surfactants. Harikrishnan et al [5] studied the spreading of sessile droplets under the influence of nanoparticles and surfactants, focusing on the interaction between surfactants and nanoparticles. For both nanocolloidal systems with and without surfactant present, they found a deviation from Tanner's Law [6] d ∝ t n , where d is the wetted diameter and t stands for time.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39] Interactions of nanofluids with solids, however, involve much more complex physical and chemical processes on different length scales behind them if, besides nanoparticles, surfactants are added to a base fluid. 40 Despite a widespread interest and intensive investigations, the information on the surfactant-laden nanosuspension wetting behavior is still quite limited and inconclusive. To the best of authors' knowledge, a recent study on spreading dynamics of nanofluids containing surfactant presented by Harikrishnan et.al.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of authors' knowledge, a recent study on spreading dynamics of nanofluids containing surfactant presented by Harikrishnan et.al. 40 is still the only work comparing wetting behavior of surfactant-laden nanosuspensions with water-based nanosuspensions and particle-free surfactant solutions. It has been found out that in complex systems consisting of nanoparticles and surfactants, the latter dominate spreading dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation